A Comparative Sectoral Analysis of Industry 4.0 Readiness Levels of Turkish SMEs - EMİR, OĞUZ; GERGİN, ZEYNEP; YÜKSEKTEPE, FADİME ÜNEY; Dündar, Uğurcan; Gençyılmaz, Güneş M.; Çavdarlı, Ali Ihsan (Springer Science and Business Media Deutschland GmbH, 2021)
The concept of Industry 4.0 brings new standards and has an essential impact on business models, work organizations, and processes. Nowadays, companies are enforced to perform such challenges as meeting personal customer requests, flexibility, responsiveness, customer-oriented solutions, and delivering continuous value to survive in the competitive market. The most innovative companies are resourceful to integrate new digital tools into their business models by following initial trends. For Small and Medium-Sized Enterprises (SMEs), adopting these new industrial challenges, and responding to them quickly is vital when it is considered that they have 99.8% of the enterprise share of Turkey. To do so, an intensive effort is needed to integrate Industry 4.0 applications within the enterprises. It has been suggested in the literature that manufacturing organizations should begin with understanding their current level of maturity by defining their strengths and weaknesses. Further, a significant effort is required with the collaboration of government, academia, and industry leaders to guide enterprises for improving their capabilities in an objective and standardized manner. Despite the diversity of approaches directed to Industry 4.0 concepts, it is not easy to find a study that measures how the manufacturing sector is adopting Industry 4.0 and compares manufacturing sectors with each other. To this end, broad research is initiated in March 2018 to identify the current situation of SMEs in Turkey. In this paper, it is intended to extend the study by providing a comparative sector analysis for manufacturing SMEs in Turkey in terms of Industry 4.0 transformation. Possible action plan suggestions are presented according to the results obtained at the end of the paper. © 2021, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
▪ International Symposium for Production Research, ISPR 2020, Antalya, 24 September 2020through, 26 September 2020. ▪ Part of the Lecture Notes in Mechanical Engineering book series (LNME).
Keywords: Assessment Models; Industry 4.0; Sectoral Analysis; Small and Medium Enterprises; Turkish Industry